Systematic Evaluation of Kinetics and Distribution of Muscle and Lymph Node Activation Measured by 18F-FDG- and 11C-PBR28-PET/CT Imaging, and Whole Blood and Muscle Transcriptomics After Immunization of Healthy Humans With Adjuvanted and Unadjuvanted Vaccines - Win, Zarni; Weiner 3rd, January; Listanco, Allan; Patel, Neva; Sharma, Rohini; Greenwood, Aldona; Maertzdorf, Jeroen; Mollenkopf, Hans-Joachim; Pizzoferro, Kat; Cole, Thomas; Bodinham, Caroline L.; Kaufmann, Stefan H. E.; et al. (Frontiers in Immunology, 2021)
Systems vaccinology has been applied to detect signatures of human vaccine induced immunity but its ability, together with high definition in vivo clinical imaging is not established to predict vaccine reactogenicity. Within two European Commission funded high impact programmes, BIOVACSAFE and ADITEC, we applied high resolution Positron Emission Tomography / Computed Tomography (PET/CT) scanning using tissue-specific and non-specific radioligands together with transcriptomic analysis of muscle biopsies in a clinical model systematically and prospectively comparing vaccine-induced immune/inflammatory responses. 109 male participants received a single immunisation with licensed preparations of either AS04-adjuvanted hepatitis B virus vaccine (AHBVV); MF59C-adjuvanted (ATIV) or unadjuvanted seasonal trivalent influenza vaccine (STIV); or alum-OMV-meningococcal B protein vaccine (4CMenB), followed by a PET/CT scan (n=54) or an injection site muscle biopsy (n=45). Characteristic kinetics was observed with a localised intramuscular focus associated with increased tissue glycolysis at the site of immunisation detected by 18F-fluorodeoxyglucose (FDG) PET/CT, peaking after 1-3 days and strongest and most prolonged after 4CMenB, which correlated with clinical experience. Draining lymph node activation peaked between days 3-5 and was most prominent after ATIV. Well defined uptake of the immune cell-binding radioligand 11C-PBR28 was observed in muscle lesions and draining lymph nodes. Kinetics of muscle gene expression module upregulation reflected those seen previously in preclinical models with a very early (~6hrs) upregulation of monocyte-, TLR- and cytokine/chemokine-associated modules after AHBVV, in contrast to a response on day 3 after ATIV - which was bracketed by whole blood responses on day 1 as antigen presenting, inflammatory and innate immune cells trafficked to the site of immunisation, and on day 5 associated with activated CD4+ T cells. These observations confirm the use of PET/CT, including potentially tissue-, cell- or cytokine/chemokine-specific radioligands, is a safe and ethical quantitative technique to compare candidate vaccine formulations, and could be safely combined with biopsy to guide efficient collection of samples for integrated whole blood and tissue systems vaccinology in small-scale but intensive human clinical models of immunisation, and to accelerate clinical development and optimisation of vaccine candidates, adjuvants and formulations.